The roles of orexins in sleep/wake regulation. (May 2017) - Mieda, Michihiro
Highlights: Disruption of the orexin system causes the sleep disorder narcolepsy. Orexin neurons stabilize wakefulness by promoting monoaminergic neurons. Two orexin receptor subtypes differentially regulate sleep/wakefulness. Orexin neurons suppress narcolepsy via at least two distinct efferent pathways. Orexin neurons regulate wakefulness according to external and internal environment. Abstract: Orexin A and orexin B are hypothalamic neuropeptides initially identified as endogenous ligands for two orphan G-protein coupled receptors (GPCRs). A deficiency of orexin signaling results in the sleep disorder narcolepsy-cataplexy in humans, dogs, and rodents, a sleep disorder characterized by excessive daytime sleepiness and cataplexy. Multiple approaches, including molecular genetic, electrophysiological, pharmacological, and neuroanatomical studies have suggested that orexins play critical roles in the maintenance of wakefulness by regulating the function of monoaminergic and cholinergic neurons that are implicated in the regulation of wakefulness. Here, I review recent advances in the understanding of how orexins regulate sleep/wakefulness and prevent narcolepsy.